2016
DOI: 10.1016/j.jash.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The association of renal artery calcification with hypertension in community-living individuals: the multiethnic study of atherosclerosis

Abstract: Hypertension (HTN) is a modifiable risk factor for cardiovascular disease (CVD). Renal artery calcium (RAC) may signal the presence of flow-limiting atherosclerotic disease that may contribute to changes in the kidney’s regulation of blood pressure. We hypothesized that RAC is independently associated with HTN. We examined a multi-ethnic cohort of 1,285 participants who underwent abdominal computed tomography (CT) scans in five US communities. After adjustment for age, gender, race/ethnicity, CVD risk factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Numerous studies have addressed the clinical importance of arterial calcification among CKD patients and cardiovascular high-risk patients [1012, 14, 1921]. Our previous study suggested that aortic calcification burden has a negative effect on postoperative renal function in renal transplant patients, [14] and the preoperative condition of aortic calcification has a significant impact on postoperative persistent hypertension after unilateral adrenalectomy in patients with aldosterone-producing adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have addressed the clinical importance of arterial calcification among CKD patients and cardiovascular high-risk patients [1012, 14, 1921]. Our previous study suggested that aortic calcification burden has a negative effect on postoperative renal function in renal transplant patients, [14] and the preoperative condition of aortic calcification has a significant impact on postoperative persistent hypertension after unilateral adrenalectomy in patients with aldosterone-producing adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…One such predictor is elevated pulse pressure (PP) hypertension, which can be seen as a marker of arterial senescence and stiffening [5][6][7][8]. A positive correlation exists between calcification in the renal arteries, hypertension, and renal disease [9][10][11]. Oxygen delivery index (DO 2 I) has also been shown to be independently associated with AKI in retrospective studies and in one prospective, randomized trial [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Aortic calcification is one of the sequelae of aortic degeneration and has recently been considered a major complication and independent risk factor for coronary artery disease, heart failure, and stroke [ 9 , 10 ]. Several studies have addressed the clinical importance of arterial calcification in patients at high risk for cardiovascular disease; however, only a few studies have demonstrated the impact of arterial calcification on renal function [ 11 – 13 ]. In addition, the clinical relevance of the aortic calcification index (ACI) with regard to postoperative renal function outcome in patients undergoing radical nephrectomy has not been well studied.…”
Section: Introductionmentioning
confidence: 99%